Student portal on IOS devices (client side) / Mohamed Mustaffa Murad Jaafar Ali - Jaafar Ali, Mohamed Mustaffa Murad (2014)
A mobile application a new trend in these modern days. Mobile application are designed to simplify access especially on smaller screen mobile devices. Mobile application are vary from personal to business used. A UiTM student accessing student portal using mobile phone, although the current system works well on normal computer, accessing on mobile devices can be hassle most time for part time student especially when on the move or busy with commitment This project focus on developing student portal for part time student. Using RAD method logy , we focus on developing student portal that part time student have basic access such as i-student, icress, contact and announcement. Here, part time student can perform update profile, course registration and view information such as billing, contact announcement and classes. We found that the application is helpful based on questionaire and demostration conducted with part time student and public. We received good feedback and hopes to see more improvement to the mobile application in term of more functionality and new interface design.